Consumo de combustível de um trator em função do tipo de pneu, da lastragem e da velocidade de trabalho - Lopes, Afonso [UNESP]; Lanças, Kléber P. [UNESP]; Furlani, Carlos E. A. [UNESP]; Nagaoka, Alberto K. [UNESP]; Castro Neto, Pedro; Grotta, Danilo Cesar C. [UNESP] (Departamento de Engenharia Agrícola - UFCG, 2003)
The objective of this study was to compare the consumption of fuel of the FWD agricultural tractor, equipped with three types of tyres (bias ply, radial and low pressure), with and without tyre water ballasting, operating in four forward speeds. The research was carried out at FCAV/UNESP, SP, Brazil, The soil was tilled using a chisel plow. A tractor with 89 kW (121 HP) engine power equipped with FWD was used in the experiment, and the tyres used had the following characteristics: radial (front: 14.9R26 and rear: 620/75R30), bias ply (front: 14.9-26 and rear: 23.1-30) and low pressure (front: 500/60-26.5 and rear: 700/55-34). The experiment was conducted in a completely randomized block design (3x2x4), with a total of 24 treatments and three replications. The results evidenced advantages for the tractor equipped with radial tyres. The ballasting condition with water in the tyres showed lower specific consumption. It was also observed that the increase of the forward speed reduced the specific consumption.

Com o presente trabalho, teve-se como objetivo comparar o consumo de combustível de um trator agrícola operando com pneus (radial, diagonal e de baixa pressão) em duas condições de lastragem (com e sem água nos pneus) e quatro velocidades de deslocamento. O experimento foi realizado na FCAV-UNESP, Jaboticabal, SP, em condição de preparo do solo com escarificador. Utilizou-se um trator 4x2 TDA, com potência de 89 kW (121 CV) no motor. Os pneus foram do tipo R1, com as seguintes características: radial (dianteiros: 14.9 R 26; traseiros: 620/75 R 30) diagonal (dianteiros: 14.9-26, traseiros: 23.1-30) e BPAF (dianteiros: 500/60-26.5; traseiros: 700/55-34). O delineamento experimental foi o de blocos casualizados, em esquema fatorial 3x2x4, com 24 tratamentos e 3 repetições. Os resultados evidenciaram vantagens para o trator quando equipado com pneus radiais. A condição de lastragem com água nos pneus ofereceu menor consumo específico. Observou-se também que o aumento da velocidade de deslocamento reduziu o consumo específico.
Fuel consumption of a tractor as a function of the tyre type, ballasting and forward speed
Keywords: agricultural tractor; tyre; consumption of fuel; trator agrícola; pneu; consumo de combustível